PENAMAAN KULINER DALAM MASYARAKAT DAYAK MAANYAN - Dwiani Septiana (Balai Bahasa Kalimantan Tengah, 2017)
The purpose of this research is to describe culinary naming in Dayak Maanyan community. This research uses the theory of onomastics as part of semantics science that learn names. The method used in this research is ethnographic research methods. According to Bramwell (2016) naming used in a society can be investigated by ethnographic research. The data for this research are collected by recording all lexicons related to culinary names and recording the understanding of Dayak Maanyan community about culinary in their society. The results indicate that in terms of word structure, culinary names in the Dayak Maanyan language have single forms, derivative forms, and compound forms. In terms of naming process, the culinary names in the Dayak Maanyan language can be grouped into seven types: naming based on similarity in shape, taste, cooking process, place of origin, borrowing from other languages, main ingredient, and arbitrary by the speakers.